Pengaruh Media Social Marketing dan Electronic Word of Mouth Positif Terhadap Keputusan Memilih Politeknik Hasnur Dengan Brand Trust Sebagai Variabel Intervening - Mariyam; Nadila Deryza Syofrin; Marhusin (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: This research aims to test and determine the direct and indirect influence between Social Media Marketing and positive electronic Word of Mouth on the decision to choose Politeknik Hasnur with Brand Trust as an Intervening Variable. This research uses quantitative research methods with an explanatory type and uses the SmartPLS data analysis method. by collecting data by distributing questionnaires to second semester and fourth semester Politeknik Hasnur students who are still active and residing in South Kalimantan with a sample of 171 respondents. The results of this test prove that Social Marketing Media has a significant influence on the decision to choose Politeknik Hasnur, positive electronic Word of Mouth has a significant influence on the decision to choose Politeknik Hasnur and Brand Trust as an intervening variable also has a significant influence on students' decisions in choosing Politeknik Hasnur Keywords: Media Social Marketing, Electronic Word of Mouth, Brand Trust, Decision